Folheações holomorfas com grupo de holonomia prescrito - Julio Leo Fonseca Quispe (2014)
Let F be a foliation de ned by a holomorphic vector eld X on a neighborhood of 0 2 C2 and let G be a group of holomorphic germs of di eomorphisms at 0. We address to the question on whether G is conjugated to the projective holonomy group associated to F. Our aim in this work is to study Lins Neto's article [2] that provides a partial solution to this problem.Teorema. Let G = fg1; :::; gg be a group of germs at 0 2 C of holomorphic di eomorphisms with leave 0 xed and such that g1; :::; g and g1 g are linearizable. Then there is a germ holomorphic vector eld X, with a singularity at 0 2 C2, such that its projective holonomy group conjugated to the group holomorphically generated by G.